Masculine stances and the linguistics of affect: on masculine ease - Kiesling, Scott F. (NORMA, 2018)
The connections between sociolinguistic conceptions of stance and the notion of affect are explored. After an explication of sociolinguistic theory, a view of stance based on three dimensions of evaluation, investment, and alignment is articulated. It is argued that low investment stances are connected to masculinity, and through that to a wider affect of ‘masculine ease.’
Disponible en ligne à https://www-tandfonline-com.proxy.bibliotheques.uqam.ca/doi/full/10.1080/18902138.2018.1431756#abstract
Keywords: approches et analyses; cours; discipline; lin2685; linguistique; masculinité; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; théorie des affects